Acceleration of OPC by CAC in binary and ternary systems: The role of pore solution chemistry. (May 2018) - Nehring, J.; Neubauer, J.; Berger, S.; Goetz-Neunhoeffer, F.
Abstract: In dry-mortar-formulations calcium aluminate cement (CAC) is often used as a set accelerator for ordinary Portland cement (OPC). However, a critical amount of CAC is able to delay not only the silicate reaction but also the renewed C3 A dissolution of an OPC. This delay can be counteracted by adding an appropriate amount of calcium sulfate (C) to the mix OPC/CAC. The initial hydration period is dominated by fast ettringite formation from CA (CAC) and CaSO4 from OPC generating early strength. High aluminum and low calcium concentrations in the pore solution probably hinder C-S-H seeding and precipitation, thus preventing alite dissolution. Aluminum has to be initially removed by precipitating hydrate phases to change the pore solution chemistry. The start of the silicate reaction is then induced by increasing the calcium concentration in the pore solution.